Triple to double trouble: a rare case report of fetal reduction of triplets to twin pregnancy - Rajashekar, Radhika; Munisamaiah, Munikrishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
There has been an increase in triple pregnancies in the last few years due to the increasing age of mothers and the use of birth control devices. To reduce the risks associated with triplets, embryo reduction (ER). The most common procedures are ultrasound-guided transabdominal injection of potassium chloride into the fetal heart or chest in trichorionic triamniotic (TCTA) pregnancies, or ultrasound-guided laser ablation or radiofrequency ablation in dichorionic triamniotic (TCTA) pregnancies (DCTA). 23-year-old GA1, who had amenorrhea for 6months with satisfactory fetal movements, came with complaints of abdominal pain. She gives history of conceiving after ovulation induction and history of fetal reduction. On presentation, patient was conscious oriented, tachycardia was present. On examination, uterus 24-28weeks size, and presented in active labour. Bed side ultrasound scan was done which showed dichorionic diamniotic twin gestation, with presence of FHR of both twins. She had a spontaneous expulsion of abortus of twin-A and twin-B and twin-C expelled with intact sac in toto. Post-delivery she had fever episodes with thrombocytopenia for which she was evaluated further. Multiple pregnancies are increasing due to developments in birth control services. Multiple pregnancy reduction improves fetal outcomes by reducing the risk of premature birth and other complications. There are reports showing that there is a higher risk of miscarriage and stillbirth in monochorionic and dichorionic triple pregnancies compared to trichorionic pregnancies and other complications such as twin-to-twin transfusion syndrome, growth inequality, twin anemia polycythemia sequence. In our case, spontaneous labor occurred at gestational age of 21 weeks, that is, before 24 weeks, and after thorough assessment of our patient, different measures were not taken to stop labor since patient came in active stage of labour. Triplet pregnancies reduced to twin pregnancies had significantly lower risks of adverse pregnancy outcomes, severe preterm deliveries, and low birthweight than nonreduced triplet pregnancies. However, triplet pregnancies reduced to twin pregnancies were potentially associated with a 5.6% increased risk of miscarriage.